Pengaruh Perencanaan Strategi Terhadap Strategi Keunggulan Bersaing Dimoderasi Oleh Turbulensi Lingkungan (Pada UKM Sentra Industri Kulit Manding, Bantul) - Sinthya Tetyasih Suroso; Sabihaini Sabihaini; Heru Kristanto (Publikasi Indonesia, 2022)
This study aims to determine the effect of strategic planning on competitive advantage strategies moderated by environmental turbulence at UKM Sentra Manding Leather Industry, Bantul. The phenomenon that is the main focus of this research is the basis used to choose a strategy to increase sales of leather handicrafts during the Covid-19 pandemic. With a competitive advantage strategy moderated by environmental turbulence. Methods of processing data with quantitative methods and analyzing data using PLS. The sampling technique used a census technique that made the population a sample of 48 SMEs. Collecting data in this study using a questionnaire. The results of the analysis in this study indicate that 1) There is a significant positive effect of strategic planning on competitive advantage strategy 2) There is a significant positive influence on differentiation 3) There is a significant positive influence on focus 4) There is a significant positive influence on low cost 5) Environmental turbulence strengthens the influence on competitive advantage.